Soil Erosion and the Problem of Silting in the Kosi Catchment - Das, K.N. (Journal of Soil and Water Conservation, 2022)
Formed of seven Himalayan stream, the Kosi 450 miles in lenght is one of the few problem rivers of the world if judged by the problems of flooding, large seale erosion and silting shifting of courses at a rapid peas, massiscale destruction of human and